Doping Engineering in the MoS2/SnSe2 Heterostructure toward High‐Rejection‐Ratio Solar‐Blind UV Photodetection. Issue 43 (25th September 2022) - Yu, Yali; Shen, Tao; Long, Haoran; Zhong, Mianzeng; Xin, Kaiyao; Zhou, Ziqi; Wang, Xiaoyu; Liu, Yue‐Yang; Wakabayashi, Hitoshi; Liu, Liyuan; Yang, Juehan; Wei, Zhongming; et al.
Abstract: The intentionally designed band alignment of heterostructures and doping engineering are keys to implement device structure design and device performance optimization. According to the theoretical prediction of several typical materials among the transition metal dichalcogenides (TMDs) and group‐IV metal chalcogenides, MoS2 and SnSe2 present the largest staggered band offset. The large band offset is conducive to the separation of photogenerated carriers, thus MoS2 /SnSe2 is a theoretically ideal candidate for fabricating photodetector, which is also verified in the experiment. Furthermore, in order to extend the photoresponse spectrum to solar‐blind ultraviolet (SBUV), doping engineering is adopted to form an additional electron state, which provides an extra carrier transition channel. In this work, pure MoS2 /SnSe2 and doped MoS2 /SnSe2 heterostructures are both fabricated. In terms of the photoelectric performance evaluation, the rejection ratio R 254 / R 532 of the photodetector based on doped MoS2 /SnSe2 is five orders of magnitude higher than that of pure MoS2 /SnSe2, while the response time is obviously optimized by 3 orders. The results demonstrate that the combination of band alignment and doping engineering provides a new pathway for constructing SBUV photodetectors. Abstract : The staggered large band offset heterojunction based on MoS2 and SnSe2 is an ideal structure for the separation of photogenerated carriers. Combined with doping engineering, a photodetector based on the doped MoS2 /SnSe2 heterostructure exhibits excellent solar‐blind UV photoresponse ability compared to the pure MoS2 /SnSe2 heterostructure. The rejection ratio is significantly improved by about five orders of magnitude.